Krisis Reputasi dan Respon Konsumen terhadap Palestine Washing McDonald’s: Efek Perceived Value dan Word of Mouth terhadap Purchase Intention Produk McDonald’s dengan Mediasi Purchase Attitude - Rory Sabina Anindita; Lindiawati, Lindiawati (Universitas Proklamasi 45, 2025)
This study examines the influence of Perceived Value and Word of Mouth on Purchase Intention in the context of McDonald’s alleged Palestine Washing, with Purchase Attitude as a mediating variable. A systematic literature review was conducted using databases such as Google Scholar, JSTOR, ScienceDirect, and open-access journals to explore the interplay between these constructs. The findings reveal that Perceived Value and Word of Mouth significantly impact Purchase Intention through Purchase Attitude as a mediator. This highlights the critical role of managing consumer perceptions, especially amidst sensitive socio-political controversies. However, a limitation of this study is the lack of public awareness about McDonald’s alleged Palestine Washing, which may affect the validity of responses. Practically, this research provides insights for McDonald’s to assess consumer purchase intentions following such controversies and suggests strategies to maintain brand trust and competitiveness. By examining marketing dynamics amid political challenges, this study offers a distinct perspective on how global brands can cultivate consumer trust and loyalty in contentious environments.